Research on the three-phase load imbalance control of the active distribution network based on the distributed power flow controller - Guo, Guowei; Zhan, Ximei; Wang, Jinfeng; Liu, Zhu; Feng, KangHeng; Peng, Fadong; Gong, Dehuang; Tang, Aihong; Xiang, Caili; Wang, Zihan (Frontiers in Energy Research, 2024)
In the background of the global commitment to low-carbon renewable energy transformation, new energy sources such as distributed wind–solar storage and charging and single-phase loads, such as electric vehicles, are connected to the distribution network. Due to the asymmetric access of load and the randomness of load power consumption, the problem of three-phase imbalance is becoming more and more prominent, and the uncertainty is increasing. In this paper, by analyzing the three-phase load imbalance problem of the distribution network, starting from the cause of three-phase load imbalance, the three-phase imbalance calculation method of the distribution network is deduced. The access mode of a distributed power flow controller in the distribution network and the three-phase imbalance compensation method are studied. The control strategy of the distributed power flow controller for the three-phase imbalance control of the distribution network is proposed. The simulation results show that the proposed method can effectively control the three-phase asymmetry problem of the distribution network, the configuration is more flexible, and the capacity utilization rate is higher.